Proposal of interdisciplinary definition of proper name -TRAD - Sipavicius Seide, Márcia (Onomástica desde América Latina, 2021)
This article makes a proposal of interdisciplinary definition of the concept of proper name based on Cognitive Onomastics (SJÖBLOM, 2010), Theory of Relevance (SPERBER &WILSON, 2001 [1995], (SEIDE & SCHULTZ, 2014), Neurolinguistics (VAN LANGENDONCK,2007) and the onomastic knowledge of the ideal speaker (SEIDE, 2021). In the first section of this article, the object of study of Onomastics and the characteristics of the onomastic subarea in which the research is included are described. In the second, considerations about proper name made by Sperber and Wilson (2001 [1995]) are integrated to the definition of proper names as a conceptual address. In the third section, the neurolinguistic discoveries and the description of the onomastic knowledge of the ideal speaker are presented and integrated and the proper name redefinition is described. In the fourth and final section of the article, some implications of this redefinition for onomastics studies are described.